The Relationship of Family Support with Compliance Drinking Medicine for Hypertension Elderly in Puskesmas Seberang Padang - LBS, Abri Madoni; Englardy, N.P (RADINKA JOURNAL OF HEALTH SCIENCE, 2023)
The prevalence of hypertension in Padang City in 2019 was 2931 cases and there was an increase in 2020 to 3010 cases. The incidence of hypertension at the Seberang Padang Health Center with hypertension cases was 433 people and 240 elderly people experienced hypertension (Dinkes, 2022). This study aims to determine the relationship between family support and adherence to taking medication in the elderly with hypertension at the Seberang Padang Health Center. This type of research is Analytical Survey with a Cross-Sectional Study design. This research was conducted at the Seberang Padang Health Center from March to September 2022. The population in this study was 240 elderly people who experienced hypertension at the Seberang Padang Health Center with a sample of 68 people. The sampling technique used is the accidental sampling technique. Computerized data processing (SPSS version 2016) using the chi-square test. The results of the study 79.4% of respondents had low medication adherence and 85.3% of respondents had negative family support. Hypertensive elderly who have low medication adherence are more common in hypertensive elderly who have negative family support, namely 73.5% compared to hypertensive elderly who have positive family support, namely 5.9%. Based on statistical tests, a p-value of 0.004 was obtained, so it can be concluded that there is a relationship between family support and adherence to taking medication in elderly hypertension at the Seberang Padang Health Center. Through the leadership of the Seberang Padang Health Center, it is hoped that the results of this study can be used as a reference in providing education to families in motivating elderly hypertensives to adhere to taking medication through health education.